2018
DOI: 10.5152/turkjsurg.2017.3820
|View full text |Cite
|
Sign up to set email alerts
|

Management of iatrogenic injuries due to endoscopic sphincterotomy: Surgical or conservative approaches

Abstract: Based on a single center experience with the management of ERCP-rP, we aimed to analyze the types of injuries, surgical options, and outcomes of patients with ERCP-rP. MATERIAL AND METHODSOver a five-year period between January 2010 and October 2015, all ERCP procedures (n=3432) that were performed at the Gastroenterology and General Surgery Clinic at Şişli Hamidiye Etfal Training and Research Objective: The best therapeutic approach for endoscopic retrograde cholangiopancreatography-related perforations remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
3
0
2
Order By: Relevance
“…An abdominal ultrasound can identify intraperitoneal or retroperitoneal free air, and the formation of abscesses. The CT is the most sensitive method for patients with suspected intestinal perforation, with a specificity of 82-90%, as it allow to observe if there is an extravasation of the contrast medium, collections, or neumoretroperitoneum 5,13,14 . In our study, all patients had a contrasted abdominal CT scan as a diagnostic method, and the most common finding was the pneuroretroperitoneum.…”
Section: Discussionmentioning
confidence: 99%
“…An abdominal ultrasound can identify intraperitoneal or retroperitoneal free air, and the formation of abscesses. The CT is the most sensitive method for patients with suspected intestinal perforation, with a specificity of 82-90%, as it allow to observe if there is an extravasation of the contrast medium, collections, or neumoretroperitoneum 5,13,14 . In our study, all patients had a contrasted abdominal CT scan as a diagnostic method, and the most common finding was the pneuroretroperitoneum.…”
Section: Discussionmentioning
confidence: 99%
“…La ecografía de abdomen puede identificar aire libre intraperitoneal o retroperitoneal, y la formación de abscesos. La TC es el método más sensible para los pacientes con sospecha de perforación intestinal, con una especificidad del 82-90%, ya que permite observar si hay extravasación del medio de contraste, colecciones o neumorretroperitoneo 5,13,14 . En nuestro estudio, a todos los pacientes se les realizó una TC abdominal contrastada como método diagnóstico, y el hallazgo más común fue neumorretroperitoneo.…”
Section: Discussionunclassified
“…Indeed, this is the best time to treat; even if the endoscopic treatment fails, early surgery can be performed and the prognosis is better [ 5 , 7 , 14 ]. Finally, some studies have shown that the mortality rate within 12 h of diagnosis and treatment was within 10%, and the difference between surgery and endoscopic treatment was small [ 10 , 11 , 15 , 17 , 24 ]. The mortality rate increased after 24 h, and the surgical mortality rate could be as high as 50% [ 4 , 5 , 13 , 16 , 18 ].…”
Section: Timing Of Treatmentmentioning
confidence: 99%
“…Iatrogenic ERCP-related duodenal perforation is a rare and fatal complication of ERCP, and the incidence ranges from 0.29% to 3.5% [4][5][6][7][8][9][10][11][12][13][14][15][16], but the highest reported mortality rate is 34.4% [13]. Due to the low incidence and high mortality, there are few large multi-centre cases.…”
Section: Introductionmentioning
confidence: 99%